Prediction of consumers’ satisfaction in the area of spa services with the application of the method of multiple regression - Mirek, Jolanta (Predykcja satysfakcji klientów w obszarze usług uzdrowiskowych z wykorzystaniem metody regresji wielorakiej, 2019)
The purpose of the research presented in the article was to attempt to measure the impact of the contentment with the involvement of particular groups of personnel in the performance of their duties on the potential satisfaction of the spa visitors. This paper includes the results of the exploratory research collected with the help of the questionnaire (distributed) among respondents, selected with the non-probability sampling method. The multiple regression analysis constituted the basic method implemented for the construction of the models explaining dependencies between variables. This article possesses research-application characteristics. In a sense it is innovative, mainly due to the implemented method of data analysis, since the author does not know any other works in which one would apply the multiple regression method for the evaluation of the satisfaction with spa healthcare services on the basis of the assessment of the personnel involvement in the performance of their duties
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 187-206